RENCANA PEMASARAN DIGITAL MELALUI GOOGLE DAN TOKOPEDIA DENGAN METODE SOSTAC (STUDI PT BUANA RANTAI BERKAT ABADI): RENCANA PEMASARAN DIGITAL MELALUI GOOGLE DAN TOKOPEDIA DENGAN METODE SOSTAC (STUDI PT BUANA RANTAI BERKAT ABADI) - Sih, Tih Sio; Sihombing, Binsar; Pandiangan, Bilson (Journal Business and Management, 2025)
Digital marketing has become an important component in the business strategy of modern companies, especially with the development of technology and easy access to online platforms. This study aims to develop an effective digital marketing plan using Google and Tokopedia platforms by applying the SOSTAC (Situation, Objectives, Strategy, Tactics, Action, and Control) methodology at PT. Buana Rantai Berkat Abadi. This study uses qualitative methods with interview techniques with company owners and direct observation. At the situation stage, internal and external environment analysis with SWOT analysis is carried out to understand the company's position in the market and identify the opportunities and threats faced by the company. The results of the study determine the company's future goals, which are described in the objectives stage. The digital marketing strategy was formulated in the Strategy stage by looking at the results of the SWOT analysis, namely the method of combining the strengths-opportunities, strengths-threats, weaknesses-opportunities, and weaknesses-opportunities strategies. Tactics will show what the company needs to do to implement the strategy. Action is described by the actions that can be taken by the company, one of which is by creating a new division that focuses on digital marketing. Then, the Control stage contains the benchmarks for the success of each activity to be carried out by the company. The results of the research with SWOT analysis and the goals to be achieved by the company in the future. The recommended segmentation is palm oil mills throughout Indonesia with a positioning as experts in the field of Mechanical Power Transmission. Then, the marketing plan has been adjusted to the results obtained in the Action and Control sections.